2023
DOI: 10.1523/eneuro.0146-23.2023
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Frontoparietal Brain Dynamics Underlying the Co-Occurrence of Autism and ADHD

Abstract: Previous diagnostic systems precluded the co-existence of autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD) in one person; but, after many clinical reports, such diagnostic criteria were updated to allow their co-occurrence. Despite such a clinical change, the neurobiological bases underpinning the comorbidity remain poorly understood, and whether the ASD+ADHD condition is a simple overlap of the two disorders is unknown. Here, to answer this question, we compared the brain dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 114 publications
(193 reference statements)
0
1
0
Order By: Relevance
“…Recent neuroimaging studies have suggested differences between pure ADHD and comorbid ADHD and ASD [65] and these two groups may need distinct treatment [66]. Future studies investigating the behavioral phenotypes of PNE humans and animals will help us to establish a more efficient treatment for comorbid ADHD and ASD in PNE children.…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuroimaging studies have suggested differences between pure ADHD and comorbid ADHD and ASD [65] and these two groups may need distinct treatment [66]. Future studies investigating the behavioral phenotypes of PNE humans and animals will help us to establish a more efficient treatment for comorbid ADHD and ASD in PNE children.…”
Section: Discussionmentioning
confidence: 99%